Postcard from Svante Arrhenius to Georg Bredig, February 1917 - Arrhenius, Svante (1917)
Postcard from Svante Arrhenius (1859-1927) to Georg Bredig (1864-1944). Arrhenius wishes Bredig a quick recovery from his sciatica and tells him about his recent birthday celebration.
Keywords: Bredig, Georg, 1868-1944; Arrhenius, Svante, 1859-1927; Chemists; Nobel Prize winners